If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p = 5(2t + -20) Reorder the terms: p = 5(-20 + 2t) p = (-20 * 5 + 2t * 5) p = (-100 + 10t) Solving p = -100 + 10t Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Simplifying p = -100 + 10t
| 0=-5x+4 | | (5a-2)(2a-3)= | | 3y+6=4y-2 | | 34=6x+2(-5x-3) | | 2y-9+y-5=13 | | -b^2+3b=0 | | 7x-10/6=3 | | b^2+10b=0 | | 5p-3=17 | | 126-3x=15x+20 | | 8x+2=5(x+4) | | a^2+7=0 | | 6x+2=9x-1 | | 5x-10=11-2x | | 0=-4.1x^2+7.1x+145 | | -n^2+8n=0 | | (5y+8)(9-y)=0 | | -3x+0=0 | | 3(x-8)-(2x-5)=32 | | -3(0)+y=0 | | 16x-2=15x+1 | | 0=-16x^2+50x+4 | | m^2+4m-6=0 | | 10x-6=7+3 | | 7x+9-2x=9x+15 | | 5(x-3)-8x=-36 | | 5x=0-9 | | 9x+9=3x+35 | | 5(0)=y-7 | | y-1.7(-3)=-2 | | y-1.7(3)=-2 | | y-1.7(0)=-2 |